2017
DOI: 10.13066/kspm.2017.12.2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Arm Training in Standing Position on Balance and Walking Ability in Patients with Chronic Stroke

Abstract: | Abstract |1 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Moreover, the treatments provided by physical therapists in South Korea tend to prioritize improvements in balance function and gait ability over the recovery of upper extremity function. However, various studies have reported that the recovery of upper extremity function can enhance functional movements [37,40,41]. A study by Bang and Cho, in which stroke patients underwent arm training, reported that improvements in balance func-tion and gait ability followed improvements in upper extremity function [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the treatments provided by physical therapists in South Korea tend to prioritize improvements in balance function and gait ability over the recovery of upper extremity function. However, various studies have reported that the recovery of upper extremity function can enhance functional movements [37,40,41]. A study by Bang and Cho, in which stroke patients underwent arm training, reported that improvements in balance func-tion and gait ability followed improvements in upper extremity function [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, various studies have reported that the recovery of upper extremity function can enhance functional movements [37,40,41]. A study by Bang and Cho, in which stroke patients underwent arm training, reported that improvements in balance func-tion and gait ability followed improvements in upper extremity function [40]. Oh and Kim reported that upper limb robotic therapy combined with conventional rehabilitation therapy could enhance upper extremity function, ADL, and cognitive function in stroke patients [41].…”
Section: Discussionmentioning
confidence: 99%